Identification of Copy Number Variants as a Suspected Cause of Cerebral Small Vessel Disease - Solomon K. Guyler; Neven Maksemous; Rodney A. Lea; Robert A. Smith; Heidi G. Sutherland; Lyn R. Griffiths (Clinical Genetics, 2026)
ABSTRACT Cerebral small vessel disease (CSVD) describes a range of neurological diseases affecting the small arteries, veins, and capillaries which supply the white matter and deep grey matter structures of the brain. They are the most common form of cerebrovascular disease, accounting for almost half of vascular dementia cases and approximately 20% of stroke incidence globally. Genetic testing is a routine diagnostic tool for monogenic CSVDs; however, less than 20% of patients have a causal variant in a known gene. Genetic testing for these disorders focuses on single nucleotide variants and short insertions or deletions, with larger genomic variation often unexplored as a cause of disease. In this study we performed whole‐exome sequencing (WES) on 111 patients suspected of familial CSVD that had previously tested negative for pathogenic variants in seven known CSVD genes ( NOTCH3 , HTRA1 , COL4A1 , COL4A2 , TREX1 , GLA , and FOXC1) . Bioinformatic analysis of WES data, multiplex ligation‐dependent probe amplification, quantitative real‐time polymerase chain reaction assays, and Nanopore long‐read sequencing were used to identify suspected copy number variants. This work identified four candidate CNVs across NOTCH3 , LMNB1 , and COL4A2 which are potential causes of CSVD and highlights the need for further investigation of more complex forms of genetic variation and their potential roles as causal of CSVD.